2019
DOI: 10.1021/acs.macromol.9b00136
|View full text |Cite
|
Sign up to set email alerts
|

Facile Strategy for Intrinsic Low-k Dielectric Polymers: Molecular Design Based on Secondary Relaxation Behavior

Abstract: An original design strategy for the preparation of polymers with a low dielectric constant is presented. The key to this design strategy is taking the most advantage of the secondary relaxation behavior of the polymer chains to obtain more free volume in the bulk, which can effectively reduce the dielectric constant of the polymer. By using this design strategy, we have successfully synthesized a novel polyimide TmBPHF with a pendant group that consists of a biphenyl unit attached to the meta-position of a phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
84
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 49 publications
(81 reference statements)
1
84
0
Order By: Relevance
“…The best k value (1.83 for c ‐T 12 B 12 ) obtained here is much lower than current state‐of‐the‐art low‐ k dielectric (i.e., porous SiCOH, k = 2.4) and recently reported low‐ k materials such as fluoropolymers, [ 18,65,66 ] modified polyimide, [ 19 ] MOFs, [ 25,26,67 ] and siloxane containing hybrid materials [ 17,68–70 ] (Table S3, Supporting Information). Although some porous organosilicas have extremely low‐ k values (≈1.7), [ 14,15 ] their further applications are limited by the inferior thermal stability (T d5 < 300 °C) and mesopore (too large pores will allow for metal diffusion through the dielectrics and result in short‐circuiting).…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…The best k value (1.83 for c ‐T 12 B 12 ) obtained here is much lower than current state‐of‐the‐art low‐ k dielectric (i.e., porous SiCOH, k = 2.4) and recently reported low‐ k materials such as fluoropolymers, [ 18,65,66 ] modified polyimide, [ 19 ] MOFs, [ 25,26,67 ] and siloxane containing hybrid materials [ 17,68–70 ] (Table S3, Supporting Information). Although some porous organosilicas have extremely low‐ k values (≈1.7), [ 14,15 ] their further applications are limited by the inferior thermal stability (T d5 < 300 °C) and mesopore (too large pores will allow for metal diffusion through the dielectrics and result in short‐circuiting).…”
Section: Resultsmentioning
confidence: 51%
“…; the other is introducing pores ( k air = 1) to decrease the density of materials. [ 4 ] The past two decades have witnessed numerous efforts that devote for reducing the k values of materials, ranging from inorganic, [ 4,10,11 ] organic‐inorganic hybrids, [ 12–17 ] to organic polymers, [ 17–23 ] and metal‐organic frameworks (MOFs). [ 24–26 ] Despite these successes, thermally and mechanically robust ultralow‐ k materials are still very scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The appealing approach toward low dielectric constant PI films for practical microelectronic application is polymer backbone structure optimization, like introducing bulky group, fluorinated and aliphatic structure via the functionalized monomers. 3436 Recently, Fang and co-workers have prepared the fluorinated polysiloxane with thermally induced cross-linking network structure, which exhibited a low dielectric constant at high frequency. 37,38 Ando reported the use of the trifunctional organosilicon to prepare low dielectric cross-linked PIs with silica and ever investigated the effects of BATMS-ODPA segment in the cross-linked PIs.…”
Section: Resultsmentioning
confidence: 99%
“…[ 6–8 ] The dielectric properties of polymeric dielectric materials are largely affected by molecular chain motion (Orientation Polarization), which is affected by temperature. [ 9,10 ] Therefore, most studies reported in recent years have focused on the high‐temperature resistant polymeric dielectric materials with excellent heat resistance and stability of thermal movement of molecular chains. [ 11–14 ] To develop various high‐temperature resistant, low dielectric constant, and low dielectric loss polymeric materials with different structures, many efforts have been done including the introduction of cross‐linked network into molecular chain [ 15–23 ] and the promotion of thermal conductivity.…”
Section: Figurementioning
confidence: 99%